2014
DOI: 10.2139/ssrn.2566245
|View full text |Cite
|
Sign up to set email alerts
|

Small Cash Rewards for Big Losers Experimental Insights into the Fight Against the Obesity Epidemic

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Thus, randomizing the size of incentives within a study can lead to new insights about the elasticity of responses across incentive sizes. A few studies on weight-loss incentives have randomized the size of the incentive, often by sizeable amounts, and have actually tended to find weak effects of incentive size on treatment effects (Jeffrey et al, 1983; Agurzky et al, 2012; Paloyo et al, 2015). Our study is the first in the literature on exercise incentives to randomize the size of the incentive holding fixed other features of the incentive and hence provides unique evidence on the elasticity of response to incentive size.…”
Section: Related Literaturementioning
confidence: 99%
“…Thus, randomizing the size of incentives within a study can lead to new insights about the elasticity of responses across incentive sizes. A few studies on weight-loss incentives have randomized the size of the incentive, often by sizeable amounts, and have actually tended to find weak effects of incentive size on treatment effects (Jeffrey et al, 1983; Agurzky et al, 2012; Paloyo et al, 2015). Our study is the first in the literature on exercise incentives to randomize the size of the incentive holding fixed other features of the incentive and hence provides unique evidence on the elasticity of response to incentive size.…”
Section: Related Literaturementioning
confidence: 99%
“…Due to the large extent of medical and detailed socio-economic information asked in the questionnaires, the dataset is suitable to investigate a variety of research questions (see e. g. Augurzky et al 2012Augurzky et al , 2015Reichert et al 2015). In the following, we give some examples: -The effect of financial incentives on weight reduction and health improvements, -The potential of cash rewards to prevent weight cycling, -Heterogeneous effects among different population groups according to socio-economic characteristics, -The relationship between weight loss and sexual activity.…”
Section: Representativeness Quality and Analysis Potentialmentioning
confidence: 99%
“…Incentive programs are not unusual for health insurers, who would like their customers to engage in healthy behavior [Stock et al 2010]. However, the use of financial incentives in the treatment of obesity and overweight still raises ethical concerns [Halpern, Madison, and Volpp 2009], and its effectiveness is not well-established with respect to the issue of weight maintenance [Jeffery 2012;John et al 2011;Augurzky et al 2015].…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies have shown that financial incentives are effective at inducing weight loss [Paloyo et al 2014], the evidence for its effectiveness at maintaining the lower weight is limited and not definitive [Reuss-Borst et al 2015;Augurzky et al 2015;Jeffery 2012]. …”
mentioning
confidence: 99%